WEBVTT
00:00:02.000 --> 00:00:11.080
In this video, weβre going to work with matrices and check out a claimed proof that the matrix one, one, zero, zero is equal to the matrix one, zero, zero, one.
00:00:14.840 --> 00:00:19.040
So letβs start off by defining matrix π΄ to be one, one, zero, zero.
00:00:20.160 --> 00:00:30.400
And if I multiply π΄ by itself, first I multiply one by one, and then I add one times zero to get this term here.
00:00:31.600 --> 00:00:37.840
Then I multiply one by one and add one times zero to get this term here.
00:00:39.800 --> 00:00:45.360
Then zero times one and zero times zero to get this term here.
00:00:47.160 --> 00:00:52.800
And lastly zero times one and zero times zero to get this term here.
00:00:54.800 --> 00:00:56.360
Well one times one is one.
00:00:56.640 --> 00:00:58.160
One times zero is zero.
00:00:58.400 --> 00:00:59.600
One and zero is one.
00:01:00.840 --> 00:01:02.080
And one times one is one.
00:01:02.800 --> 00:01:03.920
One times zero is zero.
00:01:03.920 --> 00:01:04.880
One and zero is one.
00:01:06.360 --> 00:01:07.720
Zero times one is zero.
00:01:07.720 --> 00:01:09.040
Zero times zero is zero.
00:01:09.040 --> 00:01:10.400
Zero plus zero is zero.
00:01:11.560 --> 00:01:14.240
And so again, zero times one is zero.
00:01:14.440 --> 00:01:15.440
Zero times zero is zero.
00:01:15.440 --> 00:01:16.880
Zero plus zero is zero.
00:01:18.360 --> 00:01:24.760
So that means if I multiply matrix π΄ by matrix π΄, by itself in other words, I get the result which is matrix π΄.
00:01:26.240 --> 00:01:31.440
Now I can premultiply both sides of my equation by the inverse matrix of π΄.
00:01:33.000 --> 00:01:46.000
And because matrix multiplication is associative, it doesnβt matter whether I multiply π΄ inverse by the result of π΄ times π΄ or whether I multiply the result of π΄ inverse π΄ by matrix π΄.
00:01:47.840 --> 00:01:49.560
In either case, weβll get the same result.
00:01:50.680 --> 00:02:00.080
Now the definition of the inverse matrix of π΄ is that when I pre multiply π΄ by its inverse, I get the identity matrix one, zero, zero, one.
00:02:01.080 --> 00:02:03.560
And Iβm doing that here and over here.
00:02:04.040 --> 00:02:08.320
So the identity matrix times π΄ is equal to the identity matrix.
00:02:09.480 --> 00:02:20.720
And because premultiplying by the identity matrix is a bit like multiplying a number by one, it gives a result thatβs equal to the original matrix, that means that π΄ is equal to πΌ.
00:02:22.200 --> 00:02:30.320
And through a series of logical steps, weβve proved that the matrix one, one, zero, zero is equal to the matrix one, zero, zero, one.
00:02:31.720 --> 00:02:38.480
Well that was all very plausible, but I can assure you that the matrix one, one, zero, zero is not equal to the matrix one, zero, zero, one.
00:02:38.480 --> 00:02:40.240
So why donβt you pause the video now.
00:02:40.520 --> 00:02:41.280
Have a look through.
00:02:41.280 --> 00:02:43.920
And see if you can work out whereabouts our logic broke down.
00:02:48.000 --> 00:02:48.200
Right!
00:02:48.200 --> 00:02:52.480
First of all, Iβm just gonna tidy this up a little bit to make some space for us to write some more things.
00:02:53.920 --> 00:02:59.880
Okay, so our first line says that π΄ is defined as being the matrix one, one, zero, zero.
00:03:00.120 --> 00:03:02.720
Well thatβs a perfectly fine matrix so thereβs no problems there.
00:03:03.920 --> 00:03:09.560
And in the next line we multiply matrix π΄ by itself and get the result one, one, zero, zero.
00:03:10.800 --> 00:03:20.320
Well the method for multiplying two two-by-two matrices together is to take this term and multiply by this term and then add this term multiplied by this term.
00:03:20.800 --> 00:03:26.800
And this gives us this term in the answer, which is π times π plus π times π.
00:03:28.000 --> 00:03:33.640
Then to get this term over here, I do π times π plus π times β.
00:03:33.640 --> 00:03:40.840
Then to get this term here, I do π times π plus π times π.
00:03:42.160 --> 00:03:47.200
Then to get this term here, I do π times π plus π times β.
00:03:48.760 --> 00:04:08.840
And indeed when I apply that logic to one, one, zero, zero times one, one, zero, zero, I do get one times one plus one times zero, one times one plus one times zero, zero times one plus zero times zero, and zero times one plus zero times zero, which is indeed one, one, zero, zero.
00:04:09.160 --> 00:04:11.280
So that second line is also correct.
00:04:12.280 --> 00:04:19.240
Then just representing the matrices by their letters, we can see that π΄π΄ or π΄ times π΄ does in fact equal π΄.
00:04:20.720 --> 00:04:26.600
Now in the next line we start talking about π΄ inverse, π΄ to the power of minus one, the inverse matrix of π΄.
00:04:27.800 --> 00:04:36.080
And the meaning of the word inverse here is the matrix that I need to multiply π΄ by in order to get the identity matrix one, zero, zero, one.
00:04:37.440 --> 00:04:45.720
So if our matrix π΄ starting off as being π, π, π, π, the inverse of π΄ is the inverse of this matrix.
00:04:47.120 --> 00:04:57.320
And this turns out to be one over ππ minus ππ times the matrix π, negative π, negative π, π.
00:04:57.320 --> 00:05:01.880
Now ππ minus ππ is a value that we called the determinant of the matrix.
00:05:02.080 --> 00:05:05.680
And thatβs quite easy to calculate for a two-by-two matrix.
00:05:05.680 --> 00:05:08.000
Itβs a bit more complicated for bigger matrices.
00:05:08.000 --> 00:05:10.440
But weβll just stick to a two-by-two matrix for now.
00:05:11.840 --> 00:05:16.760
And then within the matrix itself, you can see that weβve swapped the π and the π over here.
00:05:16.760 --> 00:05:19.760
And weβve taken the negative of π and π.
00:05:21.360 --> 00:05:29.160
So when we define the inverse matrix in that way, we find that π΄ inverse times π΄ gives us the identity matrix one, zero, zero, one.
00:05:29.160 --> 00:05:32.040
Letβs run through and see it in action.
00:05:32.040 --> 00:05:44.160
With π΄ being defined as matrix π, π, π, π and the inverse of π΄ being one over the determinant times π, negative π, negative π, π, weβve got π΄ inverse π΄ is equal to all that lot.
00:05:46.040 --> 00:05:49.840
Now this is just a constant times every term in the resultant matrix.
00:05:49.840 --> 00:05:54.320
So letβs multiply these two matrices together using the method that we talked about earlier.
00:05:55.520 --> 00:06:02.080
Weβre gonna have to do π times π add negative π times π for this term up here.
00:06:03.480 --> 00:06:11.240
Then itβs going to be π times π add negative π times π for this term over here.
00:06:11.480 --> 00:06:16.280
Then negative π times π add π times π for this term down here.
00:06:17.920 --> 00:06:22.680
And finally, negative π times π plus π times π down here.
00:06:24.600 --> 00:06:27.360
Now π times π is the same as π times π.
00:06:27.360 --> 00:06:31.920
And then if weβre adding negative π times π, thatβs the same as taking away π times π.
00:06:33.080 --> 00:06:36.360
So I can rewrite that term as ππ minus ππ.
00:06:37.640 --> 00:06:47.880
Then ππ, adding the negative of π times π, well thatβs the same as π times π take away π times π, which is nothing or zero.
00:06:48.560 --> 00:06:53.080
And then negative ππ plus ππ, well π times π is the same as π times π.
00:06:53.080 --> 00:06:55.720
So this is negative ππ plus ππ.
00:06:55.720 --> 00:06:56.760
That again is zero.
00:06:57.840 --> 00:07:01.480
And then down here, negative ππ is the same as negative ππ.
00:07:01.800 --> 00:07:07.480
And if I write these two in a different order, I get ππ minus ππ.
00:07:07.480 --> 00:07:12.400
And now, I have to multiply each of the terms in that matrix by the constant term outside.
00:07:13.400 --> 00:07:16.440
And of course zero divided by ππ minus ππ is just zero.
00:07:16.640 --> 00:07:19.920
And ππ minus ππ divided by ππ minus ππ is just one.
00:07:20.920 --> 00:07:29.640
So in general, yes the inverse of π΄ times π΄ does give us this identity matrix, πΌ: one, zero, zero, one.
00:07:31.440 --> 00:07:36.080
But letβs take a look at the specific case when the matrix π΄ is one, one, zero, zero.
00:07:37.200 --> 00:07:43.560
Then the inverse of π΄ is going to be one over the determinant times β well I need to swap over the zero and the one here.
00:07:44.560 --> 00:07:47.840
And I need to take the negative of the one and the zero here.
00:07:49.720 --> 00:07:52.080
Well of course, negative zero is just zero.
00:07:52.960 --> 00:07:56.400
So Iβve just gonna write that in here and then I can work out what the determinant is.
00:07:57.160 --> 00:08:01.840
Well itβs one times zero minus one times zero.
00:08:03.200 --> 00:08:05.720
And one times zero is zero.
00:08:05.720 --> 00:08:10.080
So that becomes one over zero minus zero.
00:08:10.080 --> 00:08:12.400
And obviously zero minus zero is zero.
00:08:15.120 --> 00:08:17.640
And weβve just set off the dividing-by-zero alarm!
00:08:18.760 --> 00:08:20.960
One divided by zero is undefined.
00:08:20.960 --> 00:08:24.040
So weβre trying to multiply this matrix by an undefined number.
00:08:25.520 --> 00:08:30.320
It turns out that the inverse of matrix π΄ is undefined.
00:08:30.320 --> 00:08:33.880
We call π΄ a singular or a degenerate matrix.
00:08:34.760 --> 00:08:39.400
And thatβs just a square matrix that doesnβt have an inverse where the determinant is zero.
00:08:40.880 --> 00:08:47.360
So going back to our so-called proof, when multiplying by π΄ inverse, weβre multiplying by an undefined number.
00:08:47.680 --> 00:08:50.920
And from then on in, everything is complete nonsense.
00:08:52.200 --> 00:08:57.360
Because the inverse of π΄ is undefined, we canβt do further calculations with undefined numbers.
00:08:58.440 --> 00:09:02.280
We havenβt proved that one, one, zero, zero is equal to one, zero, zero, one after all.
00:09:04.680 --> 00:09:05.800
It was a fake proof.